The Self-Destruction of Madame Bovary: Toward a Political Economy of Pleasure (2023)
In this article, we consider the construction of Emma Bovary’s subjectivity, situating it within the discourse of love articulated by her, which is profoundly modern. Simultaneously, a social reading of the perpetual dissatisfaction that describes the character is conducted, analyzing aspects of her sensitivity that align with the logic of perpetual accumulation established by the capitalist production system, even at the level of subjectivity. This article’s primary objective is to provide a socio-historical perspective to Flaubert’s work and reflect on the ambivalent role that the protagonist plays in it.